Political Participation of Women in Brazil: From the Application of Quotas to Effective Parity in Representation - Quintela, Débora Françolin (2016)
This article proposes that gender equality and, therefore, the presence of women in politics are necessary conditions for contemporary democracies. It does not suffice that women, who represent more than half of the Brazilian electorate, are entitled to vote if they do not participate in the decision-making arenas equally to men. Based on an analysis of the effectiveness of the quota law in Brazil, this paper proposes the implementation of gender parity in the composition of the legislature, an issue which is under widespread discussion across Latin America but which is not yet being addressed in Brazilian politics.